A Practical Protocol for the Hiyama Cross-Coupling Reaction Catalyzed by Palladium on Carbon - Monguchi, Yasunari; Yanase, Takayoshi; Mori, Shigeki; Sajiki, Hironao (Synthesis, 2013)
A method for the palladium on carbon (Pd/C) catalyzed cross-coupling reaction between aryl halides and trialkoxy(aryl)silanes in the presence of a small amount of water is established using tris(4-fluorophenyl)phosphine as the ligand. A range of biaryl compounds is prepared using this protocol.
Keywords: palladium; cross-coupling; heterogeneous; silicon; biaryls